Regulasi Diri Anak Panti Asuhan Ahmad Yani Pontianak - Alifah Maulidiya (Program Studi Bimbingan dan Konseling Islam (BKI) Fakultas Ushuluddin, Adab dan Dakwah (FUAD) Institut Agama Islam Negeri (IAIN), 2025)
This study aims to understand the dynamics of self-regulation in children living in the Ahmad Yani Pontianak Orphanage. Self-regulation is an individual's ability to control emotions, behavior, and thoughts in achieving certain goals. Children in orphanages have diverse life backgrounds, often colored by traumatic experiences that can affect their ability to adapt to environmental rules and pressures. This study uses a qualitative approach with a case study method, involving four main subjects selected purposively based on certain criteria. Data were collected through in-depth interviews, observations, and documentation, then analyzed using the Miles and Huberman approach. The results of the study showed variations in the level of self-regulation in orphanage children, which were influenced by internal factors such as emotions and past experiences, as well as external factors such as the social environment, parenting patterns, and routines in the orphanage. Some children showed good self- regulation skills, while others still had difficulty adjusting, controlling emotions, and understanding the meaning of the rules applied. This study emphasizes the importance of an empathetic approach, consistent habituation, and environmental support in helping orphanage children develop optimal self- regulation.